The uniqueness of human social ontology - C. Runehov, Anne L. (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
Darwin’s theory of evolution argued that the human race evolved from the same original cellas all other animals. Biological principles such as randomness, adaption and natural selection led to the evolution of different species including the human species. Based on this evolutionary sameness, DonaldR. Griffin (1915-2003) challenged the behaviourist claim that animal communication is characterized asmerely groans of pain. This paper argues that (1) all animals are embedded in a social system. (2) However,that does not mean that all animals are social animals. (3) That the human social ontology remains to beunique due to a gene-cultural co-evolution.